Modelo MCLP : consideraciones a múltiples coberturas (2016)
The Localization problems cover a wide field in Operations Research and Logistics, in these the best location for potential installations is seek, considering a set of constraints and depending on the specific objectives of the model: Minimize costs, maximize coverage, among others. The Maximal Covering Location Problem model is a problem that seeks to maximize coverage on demand, strategically locate facilities or service points. Since the origin of this model, many others have emerged seeking to improve the limitations they present, the new models also have quite important limitations or have assumptions that bring a lot of bias. In this paper a new alternative of the MCLP model is proposed, which seeks to correct the existing limitation when multiple installations are activated simultaneously. Likewise, the new model still presents limitations, so a heuristic way of applying the new model is proposed. This project seeks to explore new alternatives for solving the problem and to lay the groundwork for future work.